Efficiency And Optimization Modelling Of Healthcare Resources For Treating Type 2 Diabetes Mellitus Patient With Basal Insulin Regimen In Malaysia - Ng, Chin Hui (2020)
The study aims to determine the optimal allocation of long-acting insulin analogues (LAIA) among patients with Type 2 Diabetes Mellitus (T2DM) within a fixed budget. The objective was achieved via a three-phase study. In the first phase, the input values for economic evaluation analysis were obtained from secondary data and cross-sectional study. The second phase involved cost-effectiveness analysis to determine the total quality-adjusted life years (QALYs) gained and costs for LAIA and NPH insulin among the targeted patients. UKPDS-OM Version 2.0 was used to estimate the impact of long-term diabetes-related complications, while simple cost-utility analysis was conducted to compare the impact of a severe hypoglycemic event between LAIA and NPH insulin usage. The outputs of these models were combined to obtain total QALY gained and the total cost over 40-year for LAIA versus NPH insulin. These values were then used as inputs for the budget optimization model in phase three. The result showed that T2DM patients treated with LAIA (especially insulin detemir) were projected to benefit from improved life year (LY) and QALYs compared to NPH insulin, especially when accounting for the impact of severe hypoglycemia. The findings from the budget optimization analysis showed that the best scenario for the additional budget was to allocate it to the high HbA1c level and elderly patients (above 60 years old), instead of the resources being equally allocated to all subgroups.